Perlukah Innovation Speed Bagi Keberlanjutan Bisnis Jangka Panjang Pada UMKM? - Sugiarto, Devan Christian (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Micro, small and medium enterprise (MSME) is one key ofeconomic growth. MSME increase economy level of the nation and alsodecrease joblessness. With a big impact, MSME also have obstacle tosurvive in a market. This issue make MSME must keep their competitiveadvantage high. One of the way is to make innovation as soon aspossible. Innovation speed can give MSME some of advantage like to befirst mover in the market. This result found that innovation speed canmake enterprise growth for long term period. Innovation speed alsosupport sustainability in the business. MSME also must pay attention tosustainability concept that business need to concern on three elementseconomy,social and environment. So, the innovation of MSME need tosynchronize with sustainability concept to have a good competitiveadvantage in the market for a long term.Keyword: Innovation speed, corporate sustainability, competitiveadvantage, micro small medium enterprise